2007
DOI: 10.1073/pnas.0709651104
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary CXCR2 regulates VCAM-1 and antigen-induced recruitment of mast cell progenitors

Abstract: chemokine receptors ͉ endothelium ͉ lung inflammation T he bronchial inflammation in atopic asthma and in allergeninduced mouse models of pulmonary inflammation is characterized by the influx of various effector cell populations including Th2 cells, eosinophils, basophils, and mast cells (MC). The MC numbers increase both in the smooth muscle and in the epithelium of the airways of humans with atopic asthma (1, 2). Moreover, there is marked hyperplasia of intraepithelial (IE) MC in mice with antigen-induced Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 30 publications
2
101
1
Order By: Relevance
“…As a consequence, W sh mice exhibit cardiac hypertrophy, a phenotype characteristic of corin-deficient mice ( Figure 6E). 24 These data confirm that the mutation underlying the W sh phenotype interrupts corin between exons 5 and 6, and encompasses 27 other genes in an inversion spanning approximately 3.1 Mb (Table 1). We cannot exclude the loss of a limited amount of genetic material at the newly 5Ј end of Gray nucleotides belong to inverted corin, underlined and italicized bases are insertions and black nucleotides are bases upstream of Kit unaffected by inversion.…”
Section: Identification Of the 3ј Inversion Breakpoint And Disruptionsupporting
confidence: 69%
See 1 more Smart Citation
“…As a consequence, W sh mice exhibit cardiac hypertrophy, a phenotype characteristic of corin-deficient mice ( Figure 6E). 24 These data confirm that the mutation underlying the W sh phenotype interrupts corin between exons 5 and 6, and encompasses 27 other genes in an inversion spanning approximately 3.1 Mb (Table 1). We cannot exclude the loss of a limited amount of genetic material at the newly 5Ј end of Gray nucleotides belong to inverted corin, underlined and italicized bases are insertions and black nucleotides are bases upstream of Kit unaffected by inversion.…”
Section: Identification Of the 3ј Inversion Breakpoint And Disruptionsupporting
confidence: 69%
“…The mast cell colonies with their distinct morphology were counted at 10 to 14 days. While committed mast cell progenitors have typically been enumerated in peripheral tissues with this technique, 24 myeloid progenitors upstream of committed mast cell progenitors that are SCF-and/or interleukin-3-responsive would also be expected to form colonies in this assay. 25 Thus this assay enumerates the cells capable of giving rise to committed mast cells within this tissue.…”
Section: Mast Cell Progenitor Assaymentioning
confidence: 99%
“…However, when sensitized mice are challenged, the influx of MCp to the lung increases 10-to 30-fold (10,12). This is followed by an increase in mature mast cells in the tracheal intraepithelium 1 wk later (11). Therefore, the allergen-induced increase in mature lung mast cells seen in both asthmatic patients and in mouse models is presumably preceded by an increased migration of MCp into the lung, referred to in this study as MCp recruitment.…”
mentioning
confidence: 85%
“…+ cells are required for MCp recruitment to the lung in sublethally irradiated wild-type mice reconstituted with CD11c-DTR bone marrow Previous studies have demonstrated that the Ag-induced recruitment of lung MCp is followed by intraepithelial mast cells that appear in the trachea 1 wk after challenge (11). To investigate whether the absence of CD11c + cells during the challenge phase leads to reduced numbers of mature mast cells in the airways, we therefore had to wait 11 d after the first DT treatment.…”
Section: Cd11cmentioning
confidence: 99%
See 1 more Smart Citation